Breast/chest feeding Support: Critically Analyzing a Canadian Policy Guiding Nursing Practice - Hermandeep Deo; Emmanuela Ojukwu; Geertje Boschma (York University Libraries, 2023)
The World Health Organization has identified the importance of improving the rates of breast/chest feeding for population health. Canadian health organizations have put public health resources toward breast/chest feeding support. Despite statements of purpose describing health promotional interventions to be focused on improving overall population health, many times these methods are based only upon biomedical knowledge and fail to adequately address the needs of diverse populations. Thus, in this paper we critique a Canadian policy providing clinical guidance to care providers through the application of a relational inquiry framework. We draw on the first author's experience as a Public Health Nurse delivering breast/chest feeding support within the scope of these guidelines to further illustrate the point. The results from published evidence are integrated within this critique to provide an evidence base for policy improvement recommendations to improve the social, cultural, and political components of breast/chest feeding typically overlooked in current standards.